Growth and antioxidant responses of Saccharomyces cerevisiae BY4741 exposed to titanium dioxide nanoparticles under heat-shock conditions - Capela-Pires, J (2014)
Nanomaterials are structures with size range between 1 and 100 nm, their strength, conductivity, reactivity and surface area/molecular size ratio, which differ substantially from macro- or micron- sized materials, shifting the rules of physics and chemistry to the sidelines. Nanoparticles have geological origin and ubiquitous occurrence in the earth crust, this can lead to suppose a good phylogenetic adaptation of living beings. However, the industrial development have contributed to raise their environmental levels of nanoparticles in certain regions of the world. The reactivity of nanoparticles with biomolecules mainly depends on the physicochemical factors such as pH and temperature. Thus, the main objective of this study was to evaluate how heat-shock affects cell survival and antioxidant response of Saccharomyces cerevisiae BY474, that suffer a loss of proliferative capacity by an active process when the level exposure was 0.1 mg/mL. However, for 1 mg/mL TiO2-NPs level, appears to occur a transition for necrosis.